South Africa : Financial System Stability Assessment, Including Report on the Observance of Standards and Codes on the following topic; Securities Regulation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper discusses the Financial System Stability Assessment for South Africa, and reviews the Report on the Observance of Standards and Codes on Securities Regulation. The assessment reveals that South Africa's sophisticated financial system is fundamentally sound and has so far weathered the global financial market turmoil without major pressures. Banks and insurance companies have enjoyed good profitability, capitalization levels, and reserves. The financial sector regulatory framework is modern and generally effective. Stress tests suggest that capital and reserve cushions at banks and insurance companies are sufficient to absorb large shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet